2019
DOI: 10.4317/jced.55576
|View full text |Cite
|
Sign up to set email alerts
|

Effect of addition of bioactive glass to resin modified glass ionomer cement on enamel demineralization under orthodontic brackets

Abstract: Background Enamel demineralization and white spot lesions around orthodontic brackets is a common problem associated with fixed orthodontic treatment. Glass ionomer cements (GICs) are commonly used for bracket bonding and recently, bioactive glass (BAG) was added to GICs to enhance deposition of calcium phosphate in adjacent dental structure. This study sought to assess the effect of addition of BAG particles to resin modified GIC (RMGIC) on enamel demineralization under orthodontic brackets. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 23 publications
1
16
0
Order By: Relevance
“…In another study, the reconstructed micro-CT images showed a reduced demineralization of dentine surface in the groups treated with fluoride products [ 23 ]. An in vitro study showed that the bioactive glass added into glass ionomer cement (GIC) can decrease the degree of enamel demineralization around orthodontic brackets [ 24 ], which is consistent with the results of the present study. An earlier study found that adding 45S5BAG fillers into sealants can prevent demineralization of enamel surfaces [ 25 ].…”
Section: Discussionsupporting
confidence: 91%
“…In another study, the reconstructed micro-CT images showed a reduced demineralization of dentine surface in the groups treated with fluoride products [ 23 ]. An in vitro study showed that the bioactive glass added into glass ionomer cement (GIC) can decrease the degree of enamel demineralization around orthodontic brackets [ 24 ], which is consistent with the results of the present study. An earlier study found that adding 45S5BAG fillers into sealants can prevent demineralization of enamel surfaces [ 25 ].…”
Section: Discussionsupporting
confidence: 91%
“…1 However, in pediatric practice, glass ionomer cements still maintain their vital role due to their remineralization effect on demineralized carious tissue. [2][3][4] A decade ago, nanofillers were integrated into glass ionomer cements and a new restoration material carbomer was developed. It was claimed to remineralize hydroxy apatite and form flouroapatite crystals.…”
Section: Introductionmentioning
confidence: 99%
“…BAG is an inorganic compound of biocompatible materials that reacts rapidly in an aqueous environment with the releases of ions, such as Ca 2+ , Na + , and PO 4 3− , which could aid in the remineralisation of the tooth structure [ 21 ]. According to Shimazi et al [ 50 ], BAG has a high ability to release ions due to its large surface and high properties due to weak ionic bonds. The easy release of calcium into the surrounding environment could inhibit demineralisation and promote remineralisation [ 19 ].…”
Section: Discussionmentioning
confidence: 99%